Uji Indeks Glikemik dan Organoleptik Keripik Berbahan Komposit Tepung Bebas Gluten yang Diperkaya Spirulina Platensis: Glycemic Index and Organoleptic Test of Gluten-Free Chips Made from Composite Flour Enriched with Spirulina Platensis - Rahma, Amalia; Supriatiningrum, Dwi Novri; Prayitno, Sutrisno Adi; Mulyani, Endah; Ariestiningsih, Eka Srirahayu (Universitas Airlangga, 2025)
Background: The World Health Organization (WHO) recommends consuming low glycemic index (GI) foods to manage blood glucose. The GI value of foods is influenced by the ratio of amylose to amylopectin and also the addition of bioactive compounds. Spirulina platensis is a type of microalgae rich in bioactive compounds, including phenolic acids and volatile compounds. Objectives: This study aimed to evaluate the glycemic index (GI) levels and organoleptic properties of chips made from gluten-free composite flour enriched with Spirulina sp. Methods: The research design was experimental. Three formulations were tested: A413 (mocaf: 30%; cornstarch: 20%; corn grits: 20%; tapioca: 30%), A531 (mocaf: 30%; cornstarch: 20%; corn grits: 10%; tapioca: 40%), A249 (mocaf: 30%; cornstarch: 10%; corn grits: 20%; tapioca: 40%). The GI testing involved 10 respondents who met the following criteria: normal BMI, aged 20-40 years, drug-free, non-smoking, non-drinking, no history of chronic diseases, not pregnant or breastfeeding. The GI value was calculated based on the area under the curve (AUC) of blood glucose measurement before and after consuming the standard and test food at 0, 30, 60, 90 and 120 minutes. Organoleptic testing was conducted using a hedonic test with 35 semi-trained panelists. Results: Formula A531 had the lowest GI value (GI = 28) among the three formulations. There was no significant difference in scent and flavor between the three formulations. However, formula A531 was the most preferred in terms of texture (p-value = 0.029) and crispiness (p-value = 0.050) compared to the other formulations. Conclusions: Gluten-free chips enriched with Spirulina sp. (Formula A531) can serve as a healthy, low-glycemic-index snack alternative that is acceptable to consumers.